2019
DOI: 10.1177/1474904119872654
|View full text |Cite
|
Sign up to set email alerts
|

Pedagogic practices in a deregulated upper secondary school: Students’ attempts to influence their teaching

Abstract: This article explores strategies, targets, and responses to young people’s attempts to influence pedagogic practices, and the variations between different programmes in a deregulated upper secondary school system. Using Basil Bernstein’s code theory, the study draws on ethnographic data from two of the most popular academic programmes in one upper secondary school in Iceland, the natural science programme and the social science programme. Students tried to a greater extent to influence the ‘how’ of their every… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 28 publications
0
2
0
Order By: Relevance
“…Previous research from the Icelandic context has indicated that students in upper secondary school would rather try to influence how pedagogical practices were carried out in the classroom than the content, such as curriculum and what they would learn (Bjarnadóttir et al, 2019). Marcus expressed how the student teachers were not invited to have an opinion on the educational content of teacher education but could be included in organizational aspects such as the length of their lunch break.…”
Section: Agency In Teacher Educationmentioning
confidence: 99%
“…Previous research from the Icelandic context has indicated that students in upper secondary school would rather try to influence how pedagogical practices were carried out in the classroom than the content, such as curriculum and what they would learn (Bjarnadóttir et al, 2019). Marcus expressed how the student teachers were not invited to have an opinion on the educational content of teacher education but could be included in organizational aspects such as the length of their lunch break.…”
Section: Agency In Teacher Educationmentioning
confidence: 99%
“…However, previous research has shown that students frequently seek private tutoring (Bray, 2007). Students in some selective Icelandic grammar schools have reported that it seems to be a matter of course to seek supplementary tutoring to be able to complete strongly framed NSP mathematics courses (Bjarnadóttir & Geirsdóttir, 2018;Bjarnadóttir, Öhrn, & Johansson, 2018).…”
Section: Mathematics As a Dividing Forcementioning
confidence: 99%